Pengaruh Pengalaman Usaha, Self Efficacy dan Self Confidence terhadap Kinerja Pelaku UMKM (Studi Kasus Di Kecamatan Medan Area) - Sibarani, Andreas Remico; Utama, Amrin Mulia; Rafiki, Ahmad (Economics, Business and Management Science Journal, 2025)
The purpose of this research is to find out how business experience influences the performance of actors, to find out how self-efficacy influences the performance of actors, to find out how self-confidence influences the performance of actors, and to find out how business experience, self-efficacy and self-confidence influence the performance of MSMEs (Study Case in Medan Area District). The population in this study was 74 MSMEs in Medan City, Medan Area District. The sample in the research was 74 MSMEs in Medan City, Medan Area District using saturated samples. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The results of the research show that there is a partial influence of business experience on the performance of the perpetrator, there is a partial influence of self-efficacy on the performance of the perpetrator, there is a partial influence of self-confidence on the performance of the perpetrator, there is an influence of business experience, self-efficacy and self-confidence simultaneously on the performance of MSMEs In Medan Area District.